2009
DOI: 10.1021/es903328b
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Fluoroimmunoassay as an Advantageous Approach for Highly Efficient Determination of Sulfonamides in Environmental Waters

Abstract: Using monoclonal antibodies labeled with Eu 3+ chelates, timeresolved fluoroimmunoassay (TRFIA) methods were developed for the determination of trace sulfamethazine (SMZ), sulfamethoxazole (SMX), and sulfadiazine (SDZ) in environmental waters. Under the optimized conditions, the developed methods offered (i) low detection limits (9.8 ng/L SMZ, 6.1 ng/L SMX, and 5.4 ng/L SDZ, based on 90% inhibition) which were about 1 order of magnitude lower than that of the enzyme-linked immunosorbent assay (ELISA), (ii) hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 45 publications
2
24
2
Order By: Relevance
“…Our results (data not shown) demonstrated that no obvious variations in the signal were noted after the addition of the heavy metal ions to the water samples (0-1 mg/L). These results are in agreement with our previous report [20].…”
Section: Tolerance Evaluation Studiessupporting
confidence: 94%
See 1 more Smart Citation
“…Our results (data not shown) demonstrated that no obvious variations in the signal were noted after the addition of the heavy metal ions to the water samples (0-1 mg/L). These results are in agreement with our previous report [20].…”
Section: Tolerance Evaluation Studiessupporting
confidence: 94%
“…However, the drawbacks of being laborious, time-consuming and solvent intensive limited their application. As an alternative, high-throughput immunoassay is a good choice for analysis of FQs from water samples, depending on their outstanding properties, the assays could screen containments from large amounts of samples in a short period of time [16][17][18][19][20]. But the methods cannot be done with an automated instrument, and cannot carry out on-site analysis for the organic pollutants because of relatively sophisticated procedures.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative method for MS, immune analysis has been applied for detecting TBBPA and has shown promising potential for detecting MTDs. The determination of target MTDs based on immunoanalysis with high sensitivity and specificity, such as timeresolved fluoroimmunoassay (TRFIA), may become a promising strategy [60,61]. Another the technique of MTD determination is the establishment of a MIP method combining nanotechnology or electrochemical technology.…”
Section: Perspectivesmentioning
confidence: 99%
“…Europium-labeled MAbs (tracers) were prepared as described in the literature [24]. Briefly, 1 mg anti-tylosin MAb and 1 mg DTTA-Eu 3+ were mixed in 50 mmol L −1 sodium carbonate buffer (pH 9.6) in an amber bottle and then kept at 4°C with stirring for over 24 h. The mixture was purified by a Sephadex 6B/G-50 column and 0.1% (w/v) BSA was added to the collected MAb-DTTA-Eu 3+ .…”
Section: Labeling Of Mab With Europium Chelatementioning
confidence: 99%